Das definições estéticas à des-definição da arte - Faria, Gabriel Pereira (2021)
This present study aims to articulate ideas from several ancient, modern or contemporary authors who approach aesthetics and arts, in order to verify the meeting between arts and philosophy and, consequently, their running together. However, we see this journey has converted in a laborious relationship, with approximations and distancings. In general the aesthetics, asreflection and discussion about arts, assumesthe task to impose a way to control an individual’s senses and perception in the specific field of the artistical universe. This took place in 18th century, when Baumgarten used the greek term “Aisthesis” to substantiate the aesthetic discipline as a type of sensible knowledge, that is, a free game between reason, sensibility and imagination. Before the systematization of aesthetics, for ancients and medievals it was taken as a philosophy of arts and metaphysics of beauty, both disentangled ofsensibility. Sensibility was not wellseen by rational authors, because it would be the source of mistakes; with aesthetics, sensibility starts conquering space in philosophical reflections about arts. In medieval world, both beauty and arts were submitted to God. Moreover, philosophy in this period was subordinated to theology and used as a support to theological inferences. With Kant and Hegel, arts philosophy enters a new perspective, synonym with aesthetics. Thus, the sensibility gains primacy and the posed question is the judgement of preference and the sublime as a condition and consequence of pleasure. Arts assists to a type of metaphycial value, since the idea of masterpiece from uniqueness, something rare and orientated to contemplation, besides disclosing what is behind it, represents something greater. The modern arts question the aesthetics’ imposition regarding to feeling, that is, the values, norms and narratives conducted to arts, and meanwhile the fine arts academies convert themselves in reserved spaces of artistic experimentation to the public, the studios belong to the artists. The modern vanguards break up with this rational and metaphysical appanage of aesthetics, besidesrupturing with norms in the artistical universe, in other words, with the shape, the matter, the contents and, mainly, the beauty. The contemporary art disconnects itsef from any aesthetic and academic-artistic prescription, proving to be adventurous, modifying the concept of arts, its definitions are fugitive, which means, art disdefines itself, and this dis-definition is to be guided by other ways, not opposite, but different of those established by aesthetics. The crisis in contemporaneity does not belong to arts, art is happening, the crisis belong to aesthetics that is not able to reflect and talk about arts in current times. Trying to solve the problem, Bourriaud presents his relational aesthetics. As a symptom of this flexible and developer moment of all cultural manifestations, in other hand, the decolonial study proposes an aesthetics and decolonial arts, an aesthesia. It is a way to give voice to Latin-American cultures, furthermore, to make visible their thinking, acting and feeling. So, we travel back to aesthetics’ origin, the sensibility totally amplified, but covering the features of local values.